ChemInform Abstract: One‐Pot Synthesis of Highly Fluorescent Pyrido[1, 2‐a]indole Derivatives through C—H/N—H Activation: Photophysical Investigations and Application in Cell Imaging. Issue 16 (April 2015) - Samala, Srinivas; Pallavi, Pragyan; Kumar, Ravi; Arigela, Rajesh K.; Singh, Gajendra; Ampapathi, Ravi Sankar; Priya, Amulya; Datta, Sunando; Patra, Abhijit; Kundu, Bijoy
Abstract A simple one‐pot protocol for the Pd‐catalyzed oxidative annulation of internal alkynes with indoles to form pyridooxindole derivatives is presented.